Influence of Oral Contraceptive Use on Adaptations to Resistance Training - Dalgaard, Line B.; Dalgas, Ulrik; Andersen, Jesper L.; Rossen, Nicklas B.; Møller, Andreas Buch; Stødkilde-Jørgensen, Hans; Jørgensen, Jens Otto; Kovanen, Vuokko; Couppé, Christian; Langberg, Henning; Kjær, Michael; Hansen, Mette (Frontiers in Physiology, 2019)
Introduction: The majority of young women use oral contraceptives (OCs). Use of OCs has been associated with lower myofibrillar protein and tendon collagen synthesis rates, but it is unknown whether OCs will limit the adaptive response of myotendinous tissue to resistance training. Design and Methods: Fourteen healthy untrained young regular OC users (24±1 yrs, fat% 32±1, 35±2 mlO2·min-1·kg-1) and 14 NOC users (non-OC, controls) (24±1 yrs, fat% 32±2, 34±2 mlO2·min-1·kg-1) performed a 10-week supervised progressive resistance lower extremity training program. Before and after the intervention biopsies from the vastus lateralis muscle and the patellar tendon were obtained. Muscle (quadriceps) and tendon cross-sectional area (CSA) was determined by MRI scans, and muscle fiber CSA was determined by histochemistry. Maximal isometric muscle strength was assessed by dynamometry while 1 repetition of maximum (RM) was determined during knee extension. Results: Training enhanced CSA in both muscle (p<0.001) and tendon (p<0.01). A trend towards a greater increase in muscle CSA was observed for OC (11%) compared to NOC (8%)(interaction p=0.06). Analysis of mean muscle fiber type CSA showed a trend towards an increase in type II muscle fiber area in both groups (p=0.11, interaction p=0.98), whereas type I muscle fiber CSA increased in the OC group (n=9, 3821±197 to 4490±313 mm2, p<0.05), but not in NOC (n=7, 4020±348 to 3777±354 mm2, p=0.40)(interaction p<0.05). Post hoc analyses indicated that the effect of OCs on muscle mass increase was induced by the OC-users (n=7), who used OCs containing 30 µg ethinyl estradiol (EE), whereas the response in users taking OCs with 20 µg ethinyl estradiolEE (n=7) did not differ from NOC. Both the OC and NOC group experienced an increase in maximal isometric strength (p<0.001) and 1RM leg extension (p<0.001) after the training period with no difference between groups. Conclusion: Use of OCs during a 10-week supervised progressive resistance training program was associated with a tendency towards a greater increase in muscle mass and a significantly greater increase in type I muscle fiber area compared to controls. Yet, use of OCs did not influence the overall increase in muscle strength related to training.